2016
DOI: 10.21451/1984-3143-ar867
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and conceptus-derived factors important for conceptus survival and growth

Abstract: Progesterone (P4) from the corpus luteum (CL) is critical for the establishment and maintenance of pregnancy and plays a major role in regulating endometrial secretions essential for stimulating and mediating changes in conceptus growth and differentiation throughout early pregnancy in ruminants. Numerous studies have demonstrated an association between elevated P4 and acceleration in conceptus elongation. A combination of in vivo and in vitro experiments found that the effects of P4 on conceptus elongation ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 102 publications
(99 reference statements)
0
9
0
1
Order By: Relevance
“…As expected, the IFNAR2 receptor, JAK1 , STAT1 and STAT2 cascade and IRF9 regulatory factor were upregulated on Days 14 and 18 following AI in pregnant cows in comfort; however, no difference was observed in all IFN pathway genes of pregnant cows under heat stress. The increase of ISGs in PMN from pregnant cows only on Days 14 and 18 may be explained by the fact that the embryo did not start to elongate before Day 10, and, consequently, there is not enough amount of IFNT leaving the uterus at this time [ 60 ]. IFNT was found to modulate IFNAR2 subunit [ 23 ], and our in vivo data demonstrate upregulated IFNAR2 but not IFNAR1 in PMN from cows in comfort.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the IFNAR2 receptor, JAK1 , STAT1 and STAT2 cascade and IRF9 regulatory factor were upregulated on Days 14 and 18 following AI in pregnant cows in comfort; however, no difference was observed in all IFN pathway genes of pregnant cows under heat stress. The increase of ISGs in PMN from pregnant cows only on Days 14 and 18 may be explained by the fact that the embryo did not start to elongate before Day 10, and, consequently, there is not enough amount of IFNT leaving the uterus at this time [ 60 ]. IFNT was found to modulate IFNAR2 subunit [ 23 ], and our in vivo data demonstrate upregulated IFNAR2 but not IFNAR1 in PMN from cows in comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone (P4) from the corpus luteum (CL) is critical for the establishment and maintenance of pregnancy and plays a major role in regulating endometrial secretions essential for stimulating and mediating changes in conceptus growth and differentiation throughout early pregnancy in ruminants [27]. Numerous studies have demonstrated an association between elevated P4 and acceleration in conceptus elongation [28,29].…”
Section: Pattern Of Progesterone Concentration For Pregnant Lactatingmentioning
confidence: 99%
“…It is produced in increasing quantities [51] [52] [53], if all is going well, by the rapidly dividing fertilized egg. The presence of βhCG enables maintenance of the corpus luteum ensuring that it will continue sufficient production of progesterone needed for implantation and maintenance especially throughout the first trimester.…”
Section: Introductionmentioning
confidence: 99%